Colonization by the endophyte Piriformospora indica leads to early flowering in Arabidopsis thaliana likely by triggering gibberellin biosynthesis - Kim, D.; Abdelaziz, M.E.; Ntui, V.O.; Guo, X.; Al-Babili, S. (Elsevier, 2017)
Piriformospora indica is an endophytic fungus colonizing roots of a wide variety of plants. Previous studies showed that P. indica promotes early flowering and plant growth in the medicinal plant Coleus forskohlii. To determine the impact of P. indica on flowering time in Arabidopsis, we co-cultivated the plants with P. indica under long day condition. P. indica inoculated Arabidopsis plants displayed significant early flowering phenotype. qRT-PCR analysis of colonized plants revealed an up-regulation of flowering regulatory (FLOWERING LOCUS T, LEAFY, and APETALA1) and gibberellin biosynthetic (Gibberellin 20-Oxidase2, Gibberellin 3-Oxidase1 and Gibberellin requiring1) genes, while the flowering-repressing gene FLOWERING LOCUS C was down regulated. Quantification of gibberellins content showed that the colonization with P. indica caused an increase in GA4 content. Compared to wild-type plants, inoculation of the Arabidopsis ga5 mutant affected in gibberellin biosynthetic gene led to less pronounced changes in the expression of genes regulating flowering and to a lower increase in GA4 content. Taken together, our data indicate that P. indica promotes early flowering in Arabidopsis likely by increasing gibberellin content.